Cellular distribution and gene expression profile during flexor tendon graft repair: A novel tissue engineering approach - Subhash C Juneja (Journal of Tissue Engineering, 2013)
To understand scar and adhesion formation during postsurgical period of intrasynovial tendon graft healing, a murine model of flexor digitorum longus tendon graft repair was developed, by utilizing flexor digitorum longus tendon allograft from donor Rosa26/+ mouse, and the healing process at days 3, 7, 14, 21, 28, and 35 post surgery of host wild-type mouse was followed. Using X-gal staining, β-galactosidase positive cells of allograft origin were detectable in tissue sections of grafted tendon post surgery. Graft healing was assessed for the cellular density, scar and adhesion formation, and their interaction with surrounding tissue. From histological analysis, it was evident that the healing of intrasynovial flexor digitorum longus tendon graft takes place in an interactive environment of donor graft, host tendon, and host surrounding tissue. A total of 32 genes, analyzed by RNA analysis, expressed during healing process. Particularly, Alk1, Postn, Tnc, Tppp3 , and Mkx will be further investigated for therapeutical value in reducing scars and adhesions.